Tumor Necrosis factor–Nelated Apoptosis‐Inducing Ligand (TRAIL) Promotes Angiogenesis and Ischemia‐Induced Neovascularization Via NADPH Oxidase 4 (NOX4) and Nitric Oxide–Dependent Mechanisms - Di Bartolo, Belinda Ann; Peta Cartland, Siân; Prado‐Lourenco, Leonel; Scott Griffith, Thomas; Gentile, Carmine; Ravindran, Jayant; Md. Azahri, Nor Saadah; Thai, Thuan; Yeung, Amanda Wing Shee; Thomas, Shane Ross; Kavurma, Mary Meltem (American Heart Association, 2015)
Background Tumor necrosis factor–related apoptosis‐inducing ligand (TRAIL) has the ability to inhibit angiogenesis by inducing endothelial cell death, as well as being able to promote pro‐angiogenic activity in vitro. These seemingly opposite effects make its role in ischemic disease unclear. Using Trail−/− and wildtype mice, we sought to determine the role of TRAIL in angiogenesis and neovascularization following hindlimb ischemia. Methods and Results Reduced vascularization assessed by real‐time 3‐dimensional Vevo ultrasound imaging and CD31 staining was evident in Trail−/− mice after ischemia, and associated with reduced capillary formation and increased apoptosis. Notably, adenoviral TRAIL administration significantly improved limb perfusion, capillary density, and vascular smooth‐muscle cell content in both Trail−/− and wildtype mice. Fibroblast growth factor‐2, a potent angiogenic factor, increased TRAIL expression in human microvascular endothelial cell‐1, with fibroblast growth factor‐2‐mediated proliferation, migration, and tubule formation inhibited with TRAIL siRNA. Both fibroblast growth factor‐2 and TRAIL significantly increased NADPH oxidase 4 (NOX4) expression. TRAIL‐inducible angiogenic activity in vitro was inhibited with siRNAs targeting NOX4, and consistent with this, NOX4 mRNA was reduced in 3‐day ischemic hindlimbs of Trail−/− mice. Furthermore, TRAIL‐induced proliferation, migration, and tubule formation was blocked by scavenging H2O2, or by inhibiting nitric oxide synthase activity. Importantly, TRAIL‐inducible endothelial nitric oxide synthase phosphorylation at Ser‐1177 and intracellular human microvascular endothelial cell‐1 cell nitric oxide levels were NOX4 dependent. Conclusions This is the first report demonstrating that TRAIL can promote angiogenesis following hindlimb ischemia in vivo. The angiogenic effect of TRAIL on human microvascular endothelial cell‐1 cells is downstream of fibroblast growth factor‐2, involving NOX4 and nitric oxide signaling. These data have significant therapeutic implications, such that TRAIL may improve the angiogenic response to ischemia and increase perfusion recovery in patients with cardiovascular disease and diabetes.